Transfer of shear stresses at steel‐concrete interface: Experimental tests and literature review. Issue 1 (18th January 2019) - Chrzanowski, Maciej; Odenbreit, Christoph; Obiala, Renata; Bogdan, Teodora; Degée, Hervé
Abstract: Shear stresses can be transferred via bond at the steel‐concrete interface without having to consider any mechanical shear connectors. The research conducted shows that the use of anti‐adhesive products, such as grease, reduce the bond at the steel‐concrete interface in push‐out tests (POTs). However, the effect is still significant, especially for fully encased steel profiles. The results of an experimental POT campaign with nine small‐scale cube specimens and two composite column specimens are presented here. Three different surface conditions were examined: a) an untreated surface, b) a surface treated with anti‐adhesive agent (formwork release oil) and c) a surface treated with PTFE spray. The resulting ultimate shear stresses were compared with the experimental results available in the literature [1–10]. How the different geometries of the specimens, the concrete age and the surface treatment conditions influence the bond strength are compared and summarized.